Peculiarities of the Intensity of Photosynthesis and Transpiration of Soy Leaves (Texas Journal of Multidisciplinary Studies, 2023)
The paper presents the results of field and vegetation experiments on the study of the relationship of photosynthetic and transpiration activity of soybean leaves in Surkhandarya region.